The Rhetoric of Covid-19 Pandemics: Insights from The Indonesian Government’s Public Media Statements - Saiful Akmal; Sarah Al-Lail; Titin Arifa Maulida (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
In response to the Covid-19 outbreak, the Indonesian government must take anticipatory steps to fight against global infections increasingly unsettling the public. Many media have highlighted the government's way of dealing with the pandemics, such as providing the latest news and information related to Covid-19. In this light, this study aims to identify the rhetorical appeals used in Indonesian government statements in times of Covid-19 pandemics and describe how those rhetorical appeals used by Indonesian government public addresses from The Jakarta Post online edition from March until December 2020. This study is expected to look at how texts and practices during the pandemic and its panic were in line with the Indonesian government to support their case. The result of this study can be used as a reference for the lecturers who want to help their students understand texts and their practices in online media. In addition, this study is expected to add new content to the study of rhetoric and discourse analysis and how the language of the pandemic is represented in the media.